PERANAN LINGUISTIK DALAM PENGAJARAN BAHASA (SEBUAH CATATAN RINGAN) - Icuk Prayogi (Universitas PGRI Semarang, 2014)
Since man first appeared on earth, human life is always filled with the change of generations: the older generation is replaced a new one and is now considered the new generation, will be replaced the newer generation, and so on. So it is with science, every time there is always a more perfect theory revision in order to be called a law; the results of scientific studies are expected to be useful for the mankind in everyday life practically. To that end, it is necessary the new generation to continue vigorously reviewing their object of study, without ruling out the role of the older generation who have inspired. Thus, the student / lecturer Indonesian-requires a new generation of highly essential-called